Miss Bunting - Thirkell, Angela (London Virago Press, 2016)
"Miss Bunting, governess of choice to generations of Barsetshire aristocracy, has been coaxed out of retirement by Sir Robert and Lady Fielding to tutor their daughter Anne, delicate, sixteen years old, and totally lacking in confidence. When Anne makes friends with Heather Adams, the gauche daughter of a nouveau riche entrepreneur, her mother is appalled. Miss Bunting, however, shows an instinctive understanding of the younger generation -- perhaps, having lost so many of her former pupils to the war, she is more sympathetic to their needs. She may be a part of the old social order, where everyone knows their place, but is wise enough to realize that the war has turned everything on its head and nothing will ever be the same again -- even in rural Barsetshire."--Page 4 of cover.
"This edition published in Great Britain in 2016 by Virago Press. First published in Great Britain in 1945 by Hamish Hamilton Ltd." -- Title page verso.
107855
Keywords: Barsetshire (England : Imaginary place) -- Fiction; Governesses; Villages; Domestic fiction; Humorous fiction